2019
DOI: 10.1016/j.vetpar.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Long-term use of yeast fermentation products in comparison to halofuginone for the control of cryptosporidiosis in neonatal calves

Abstract: A B S T R A C TThe objective of this study was to compare the effect of non-GMO Saccharomyces cerevisiae fermentation products (SCFP) with that of a halofuginone treatment against Cryptosporidium parvum infection in pre-weaned calves on a commercial dairy farm. A total of 123 neonatal female calves, housed in individual hutches, were enrolled sequentially based on date of birth in 41 blocks of 3 animals each. Calves within each block were allocated to one of 3 treatments: remaining untreated, fed with SCFP (Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 47 publications
0
34
1
1
Order By: Relevance
“…Cryptosporidium parvum oocysts were obtained from experimentally infected calves kept at the large animal stable facility of the Institute of Parasitology, Faculty of Veterinary Medicine, University of Leipzig, Germany, as reported elsewhere [ 47 ]. The C. parvum strain used here belonged to the subtype 60-kDa glycoprotein (gp60) IIaA15G2RI, which is the most commonly zoonotic subtype to be found in Germany as well as in most other industrialized countries [ 48 , 49 , 50 , 51 ]. Oocyst stocks were stored in sterile phosphate buffered saline (PBS, pH 7.4) supplemented with 100 UI penicillin and 0.1 mg streptomycin/mL (P4333, Sigma-Aldrich, Darmstadt, Germany) at 4 °C for a maximum of three months to guarantee infectivity of sporozoites.…”
Section: Methodsmentioning
confidence: 99%
“…Cryptosporidium parvum oocysts were obtained from experimentally infected calves kept at the large animal stable facility of the Institute of Parasitology, Faculty of Veterinary Medicine, University of Leipzig, Germany, as reported elsewhere [ 47 ]. The C. parvum strain used here belonged to the subtype 60-kDa glycoprotein (gp60) IIaA15G2RI, which is the most commonly zoonotic subtype to be found in Germany as well as in most other industrialized countries [ 48 , 49 , 50 , 51 ]. Oocyst stocks were stored in sterile phosphate buffered saline (PBS, pH 7.4) supplemented with 100 UI penicillin and 0.1 mg streptomycin/mL (P4333, Sigma-Aldrich, Darmstadt, Germany) at 4 °C for a maximum of three months to guarantee infectivity of sporozoites.…”
Section: Methodsmentioning
confidence: 99%
“…Supplementation of SCFP has been shown to have positive impacts on performance, health, and immunity in humans and multiple animal species, including swine, poultry, and cattle ( Moyad et al, 2009 ; Shen et al, 2011 ; Brewer et al, 2014 ; Alugongo et al, 2017 ). In preweaned calves, SCFP added to the milk and starter grain have beneficial effects on rumen development and the gut microbiota and improve the outcome of Salmonella enterica challenge and Cryptosporidium parvum infection ( Brewer et al, 2014 ; Vázquez Flores et al, 2016 ; Vélez et al, 2019 ). Anecdotal reports from the field have suggested that SCFP supplementation may also improve the outcome of BRD in young calves, in dairy heifers when transitioning to group pens and freestalls, and in feedlot animals.…”
Section: Introductionmentioning
confidence: 99%
“…Four trials were assessed to have a low risk of bias (De Waele et al ., 2010; Trotz-Williams et al ., 2011; Al Mawly et al ., 2013; Vélez et al ., 2019). Diagnosis of C. parvum infection was mostly based on clinical presentation, sometimes informed by herd history.…”
Section: Resultsmentioning
confidence: 99%
“…Healthy animals should be attended before sick animals as part of daily husbandry routines. Whether higher nutritional planes can make calves more resistant to morbidity from cryptosporidiosis has been tested in other experiments without conclusive advantages for any specific nutritional strategy (Meganck et al ., 2014; Wells and Thomson, 2014; Vélez et al ., 2019; Brainard et al ., 2020 a ).…”
Section: Discussionmentioning
confidence: 99%